Study of the Physical Layout of Pangkajene Central Market Based on the Indonesian National Standard (SNI) for Traditional Markets as a Basis for Planning and Arrangement - Kamaruddin, Nurhayati; Baharuddin, Hasniar; Haq, Izharul (Journal Of Architectural Design & Technology, 2025)
Pangkajene Central Market is one of the largest traditional markets in Sidenreng Rappang Regency, South Sulawesi, and plays a vital role in driving the local community’s economy. However, the market continues to face various challenges related to service quality and the adequacy of its physical infrastructure. Traditional markets are often associated with poor environmental conditions, suboptimal services, and a lack of supporting facilities. Issues such as disorganized spatial layout, limited parking accessibility, inefficient vendor zoning, and inadequate loading and unloading areas highlight the urgent need for market restructuring. While the Sidenreng Rappang Regency Government has shown commitment to improving public infrastructure, including traditional markets, a comprehensive plan for the revitalization of Pangkajene Central Market is still lacking. This study employs an analytical approach based on the variables outlined in the Indonesian National Standard (SNI) for traditional markets to identify current problems and provide an initial overview of the potential and needs for physical restructuring. The results of this research are expected to serve as a preliminary reference for planning a more decent, well-organized traditional market that effectively supports economic activities and user comfort.